Seneca már (megint) nem a régi: A young adult fantasy és az antikvitás az Időfutár tükrében - Pataki, Elvira (Studia Litteraria, 2019)
The article examines antiquity in the most successful young adult novel series in recent times, Időfutár. The text, which intertwines the genres of fantasy and alternative historical fiction, is built upon parallel time-travelling narrative schemes, the pathos of quest fantasy is replaced by absurd humor, Greek mythology by Roman history and some classical literary models. The plot takes place during Nero’s reign and it interweaves ancient artifacts and Latin literature with state-of-the-art scientific and technical developments, to create the symbiosis of modernity and antique culture. This bears an even more significant message in the era when the ancient languages and cultures, which provide the basis of European intellect, lose importance globally.